A descriptive analysis of anglicism in Ecuadorean magazines - Galeas, Marco Vinicio (2012)
The theme investigated in this research refers to a descriptive analysis of Anglicism in Ecuadorian magazines. This research took place in Nueva Loja, Sucumbíos province. The whole information about Anglicism was obtained from different Ecuadorian magazines, such as cultural, scholarly and general interest magazines, commonly read in the place or area of investigation. This research makes reference to the descriptive analysis of Anglicism with the purpose of identifying the different linguistic behaviors in the semantic, syntactic, and morphological field, which is used by writers in Ecuadorian magazines. Anglicism were taken and listed in tables, and checked according to the rules and acceptance of the two legal dictionaries (Real Academia de la Lengua and Merriam Webster), and after that, the words were analyzed according to the qualitative and quantitative methods to determine the differences and the number of repetitions given in each magazine. The most used thirty Anglicism were chosen to analyze syntactically, morphologically and semantically. It is important to remark that, ten Anglicism were taking for each variable in different fields, to be analyzed. According to the obtained results, the General Interest Magazines use more Anglicism than the others, like technology, fashion and economy. On the other hand, the Cultural Magazines use 2 less Anglicism than the others in their headlines or texts, because writers take care about this, when they write or explain about any topic, in this kind of cultural magazines.